Structure-magnetic property relations in FeNbO4 polymorphs: A spin glass perspective. (June 2019) - Lakshminarasimhan, N.; Kumar, A.K. Nanda; Chandrasekaran, S. Selva; Murugan, P.
Abstract: Spin glass state originating from the magnetic frustration due to the geometric arrangement or cation disorder is an interesting topic of research. FeNbO4, exhibiting multifarious applications, crystallizes mainly in three different polymorphic forms with cation ordered and disordered structures. Despite their antiferromagnetic nature, the orthorhombic ( o -FeNbO4 ) and monoclinic FeNbO4 ( m -FeNbO4 ) polymorphs exhibit a difference in their magnetic properties at low temperatures. Here, we report our observation of spin glass behaviour of o -FeNbO4 with a cation disordered structure. Our work is a combined experimental and theoretical study of structure-magnetic property relations of the antiferromagnetic o - and m -FeNbO4 with the Néel temperatures of 30 and 46 K, respectively. o -FeNbO4 contrasted itself from m -FeNbO4 as a spin glass by exhibiting field-dependent bifurcation in ZFC and FC magnetization, frequency-dependent AC susceptibility, memory effect, thermoremanence, and anamoly in the heat capacity. The presence of antiphase domains and boundaries due to cation order/disorder in both the structural polymorphs was evidenced from the electron diffraction analyses that account for the observed low temperature magnetic interactions. Further, modeling the structures with varying amounts of cation disorder using first principles calculations revealed the structural stability and competing spin interactions that support our experimentally observed spin glass behaviour of o -FeNbO4 . Graphical abstract: Orthorhombic FeNbO4 with random arrangement of Fe and Nb atoms in the lattice distinguishes itself from the monoclinic polymorph as a spin glass. Image 1